A detailed approach on multiple myeloma and its treatment - Sagar, A. Veerendra; ., Ch. Divya; Prathyusha, A.; Haritha, P. (International Journal of Basic & Clinical Pharmacology, 2017)
Multiple myeloma is a cancer formed by malignant plasma cells. Normal plasma cells are found in the bone marrow and are an important part of the immune system. The immune system is composed of several types of cells that work together to fight infections and other diseases. Lymphocytes are the main cell type of the immune system. There are 2 major types of lymphocytes: T cells and B cells. When B cells respond to an infection, they mature and change into plasma cells. Plasma cells make the antibodies that help the body attack and kill germs. Lymphocytes can be found in many areas of the body, such as lymph nodes, the bone marrow, the intestines, and the bloodstream. Plasma cells, however, are mainly found in the bone marrow. Bone marrow is the soft tissue inside some hollow bones. In addition to plasma cells, normal bone marrow has cells that make the different normal blood cells. When plasma cells become cancerous and grow out of control they can produce a tumor called a plasmacytoma. These tumors generally develop in a bone, but they are also rarely found in other tissues. If there is only a single plasma cell tumor, it is called an isolated plasmacytoma. When there is more than one plasma cell tumor, it is called ‘multiple myeloma’. There are lot of plasma cell abnormalities, but multiple myeloma causes severe bone pain, so here we covered detailed notes on the disease and its treatment strategies.